Development Strategy of Village Owned Enterprises (BUMDes) in an Effort to Improve Community Welfare at Tropodo Village Sub-District of Krian Sidoarjo Regency - Farida, Fira Luluk; Choriyah, Ilmi Usrotin (JPAP: Jurnal Penelitian Administrasi Publik, 2024)
The aim of this research is to analyze the Development Strategy of Village-Owned Enterprises (Bumdes) In Efforts to Improve Community Welfare at Tropodo Village Sub-District of Krian Sidoarjo Regency. The method used in this research is descriptive qualitative. Data collection techniques use primary data obtained through interviews and secondary data obtained through observation, documentation, and journals. The author uses data analysis techniques from Miles (Sugiyono, 2013) namely, data collection, data reduction, data presentation, and drawing conclusions. The results of this research show that th strategy for developing village-owned enterprises (BUMDes) namelu, first, human resources has been successful because changes in management structure have provided better development with the presence of far more business units. Second, for the management fund BUMDes Bumiasih has strategy that is able to provide a much wider source of funds. Third, regarding technology and information the use of e-mail and ms excel is the preferred technology to use. Fourth, facilities and infrastructure many changes have been made to futher develop BUMDes Bumiasih business units.